Evaluation of heteroplasmy detection in the Ion Torrent PGM. (December 2015) - Magalhães, S.; Marques, S.L.; Alves, C.; Amorim, A.; Alvarez, L.; Goios, A.
Abstract: The use of mitochondrial DNA (mtDNA) heteroplasmy in forensic genetics casework and databasing has been limited due to the technical limitations of the PCR/Sanger sequencing technology. Massively Parallel Sequencing (MPS) has been suggested to be more sensitive and accurate in detecting and evaluating heteroplasmy levels than Sanger sequencing, particularly when contamination is controlled and the amplification strategy is carefully designed. In this work, we present the results of a sensitivity study of heteroplasmy detection and quantification with Ion Torrent PGM, using control samples of predetermined haplotypes belonging to different haplogroups. The amplification strategy used for the PGM sequencing is based on a single long-range PCR, in order to even the proportions of the mixed bases throughout the molecule. To simulate different levels of heteroplasmy we used mixtures of the amplified control samples (amplicons) at variable proportions. The PGM sequencing strategy accurately detected all artificial heteroplasmies ≥5%, with the exception of variants at repetitive regions. At the 1% level, some of the mixed bases were detected although the false positive background noise does not allow for a trustworthy variant call.